MEDIA INTERAKTIF, KOMUNIKASI EFEKTIF: ANIMATED EDUCATIONAL VIDEOS UNTUK PENGUATAN KOSAKATA DAN KEMAMPUAN BERBICARA BAHASA INGGRIS SISWA SD DALAM KONTEKS SEHARI-HARI - Endang Susilowati; Etika Dewi Kusumaningtyas; Eka Fanti Sulistiyaningsih; Tiara Nurwanti; Regita Ika Wulandari (LPPM AN Nuur, 2026)
Background: Vocabulary mastery is crucial to English speaking skills, yet many elementary school students struggle to remember and use vocabulary effectively in daily communication. This is often due to conventional teaching methods that lack engagement and effectiveness. Objective: This Community Service Program (PkM) aims to enhance students’ vocabulary acquisition and speaking skills through animated educational videos as interactive and engaging learning media. The main objective is to help students develop English vocabulary relevant to everyday life and improve their speaking abilities. Method: The program was implemented using a systematic approach comprising five main stages: needs analysis, planning, program implementation, evaluation, and follow-up. It involved 28 sixth-grade students, and the data were gathered through observations, discussions, and interviews.Results: The results indicate that animated educational videos enhanced students’ vocabulary mastery, motivation, and speaking confidence. Students became more enthusiastic, actively participated, and showed greater willingness to speak English during activities. Conclusion: In conclusion, animated educational videos effectively create engaging, interactive, and contextual learning environments and can serve as an innovative strategy to improve the quality of English language learning at the elementary level.